Role of hematinic and zinc deficiencies in recurrent aphthous stomatitis: A Review - Yuli Fatzia OSSA (Dentistry Faculty, 2020)
Hematinic has an essential role in the human body. Suppose its deficiency can cause oral disorders such as aphthous stomatitis. Recurrent aphthous stomatitis is the most common oral lesion. It has three types of clinical appearance, namely minor, central, and herpetiform. The main components of hematinic are folate, vitamin B12, folic acid. Apart from hematinic, another nutrient that can correlate with recurrent aphthous stomatitis is zinc. This review explains the relationship between hematinic deficiency and zinc associated with recurrent aphthous stomatitis.